Analysis of the mandibular molars root canals morphology. Study by computed tomography - Mantovani,Verônica de Oliveira (2022)
Abstract This study aimed to analyze the root and root canal morphology of mandibular first and second molars using CBCT images. A total of 2,400 mandibular molars exams were selected from 600 patients aged between 18 and 75 years. The number of roots, number of root canals, and root canal configuration according to the Vertucci classification were verified. Overall, 94.92% of mandibular first molars and 90.17% of mandibular second molars had two separate roots. Among the biradicular molars, the first molars showed a greater incidence of type IV canals in the mesial root and type I in the distal root. In the second molars, the most common canal form was type IV in the mesial root and type I in the distal root. In the triradicular molars, the type IV and type I configurations were the most common in the mesial root of the first molar and second molar, respectively. In both triradicular molars, there was a prevalence of type I canal in the distal and DL roots. Statistical analysis was performed at a significance level of 0.05. The number of roots was correlated with gender (Spearman test), and the canal's configuration with gender and bilaterality (Wilcoxon test). The subpopulation studied has a high incidence of bilateral symmetry and mandibular molars with two roots with two distinct mesial canals and one distal canal. The bilateral configuration is possible to estimate the number of canals, especially in images that are difficult to visualize, such as atresic canals.